A study of factors influencing the technical efficiency of cereal farms in Algeria: A case study of the Municipalities of Saida Province - Zineb Hamdene; Azzeddine Nezai; Noureddine Abdellah (Dirassat Journal Economic Issue, 2022)
Cereals are the major food for the population and an important strategic crop, and the main pillar of food security in Algeria. Province Saida is considered a pioneer in the production of cereals, but its efficiency remains below what is required. This study measured the effect of the explanatory factors represented by climatic factors, the amount of financing, and the provision of rural housing on the technical inefficiency of wheat production for the municipalities of Saida Province using the method of stochastic frontier analysis during the period 2015/2020. The results of the study showed that the evaluation of the frontier production function according to the method Maximum Likelihood was according to the random model, and that the elasticity of each of the cultivated land, irrigated land, fertilized land, and mechanization reached (0.62, 0.28, 0.98, 0.5), respectively. The results also showed that technical inefficiency affected the variation in cereal production in Saida province and that the phenomenon of inefficiency remains important in the cultivation of cereal in Saida Province and must be adopted in production models.